RESULTS OF LOCAL ЕLECTIONS IN BOGATIĆ МUNICIPALITY FROM 1992 TO 2023 - LOCAL AUTONOMY OR LOCAL POLITICAL MIMETISM? - Stančetić, Veran; Mijatović, Marko (Political Review, 2026)
This paper presents the results of local elections in the municipality of Bogatić in the Mačvan administrative district from the introduction of the multi-party system until 2023. The objective is to provide a description and explanation of the local electoral processes in this Mačvan municipality and to point out the volatility of the citizens’ electoral will, with a focus on the phenomenon of replicating coalition central to the local level. Local elections in Bogatić were held in seven equal four-year election cycles, with the electoral system being changed as many as five times in the observed period.
Keywords: Local self-government; Local democracy; Local elections; Political parties; Vertical political emulation; Republic of Serbia; Government mirroring; Bogatić municipality